Safety analysis of modern heritage masonry buildings : box-buildings in Recife, Brazil - Carvalho, Jenner (2014)
Box-buildings are structural masonry buildings named as such because of their shape. There are around 5,000 of them in Recife, Brazil. This paper presents a safety analysis of one box-building that suffered collapse on December 2007. The research aims at quantifying the safety of this type of existing buildings and at better understanding their structural behavior to try to identify the reasons for the collapse. A finite element model was prepared and a set of nonlinear numerical analyses were performed. The results of the analyses show good agreement between the observed damage in the real building and the damage achieved numerically at the current condition (LF=1). The model thus seems to represent satisfactorily the real behavior of the building but the safety factor obtained seems too conservative and does not justify the collapse observed in reality. Since results show that the building should not have failed under normal working conditions, a collapse assessment about why the building fell is therefore provided and a sensitivity analysis was performed in order to understand the importance of the material parameters and their influence on the structural response of the building.